Comparative study of antibacterial activities of ethanol extracts of the bark and seeds of garcinia kola and caricapapaya (2011)
A comparative study of the antimicrobial activities of the bark and seed extracts of Garcinia kola and Carica papaya were tested using the Agar well diffusion method on eight bacterial strains - Staphylococcus aureus; Salmonella typhi B; Shigelladysenteria; Pseudomonas aeruginosa; Serratiamarcescens; Pseudomonas fluorescens; Proteus vulgaris; and Bacillus subtillis. Phytochemical screening shows that both bark and seed of the two plants contain reducing sugars, phenols and alkaloids whereas the pawpaw extracts contained tannins which were absent in the bitter kola plant part. Garcinakola on the other hand has saponin that was not present in Caricapapaya. The Garcinia seed ethanol extract manifested the best inhibitory activities against the test bacteria, producing inhibition zones ranging from 12–23mm. There was no resistance from any of the test bacteria. The pawpaw seed extract was also effective against the test bacteria. The inhibition zone observed ranged from 11-16mm. The ethanol extract of both plants were active against Staphylococcus aureus, Shigelladysenteria, Pseudomonas fluorescens; and Salmonella typhi B. Pawpaw leaf ethanolic extract significantly inhibited Pseudomiasaeruginosa, while Garcinia seeds ethanolic extract also inhibited Bacillus substilis. The activity index of ethanol extract of Garcinia kola seed was higher than that of pawpaw seed when both gentamicin and tetracycline were used as a standard antibiotics. The aqueous extract of both plant parts were not as effective as the ethanol extract. The activities of these medicinal plants against the tested bacterial species in this study justified their common use in African traditional medicine in the treatment of various ailments.